KOMBINASI CASCADE AERATOR DAN ADSORBSI ZEOLITE DALAM MENURUNKAN KADAR Fe TERLARUT DI AIR SUMUR - Tuhu Agung Rachmanto; Farhan Septiari Wibisono (EnviroUS, 2021)
The problem that is often found in well water is the high content of iron (Fe). This study aims to reduce the content of Fe in water well with aeration and adsorbtion systems. Aeration used is a cascade aerator using two wide variety of cascade which the height of each steps are 20 cm. zeolite sand with a diameter 8 mesh.. The sample was taken at one of the community wells in the Sukodino area of Sidoarjo. The study was conducted for three days with a processed sampling system carried out on the aerator output and both adsorbtion. The results showed that the aeration process with cascade aerator was able to reduce Fe levels up to 61,93 % and 74.58%. While the adsorbtion process with zeolite media can reduce Fe levels by 86,12% and 96.81%.